Filsafat Ketuhanan Perspektif Rāmānuja Kajian Teks Vedārtha-Saṃgraha Dan Śrī-Bhāṣya - Ni Kadek Surpi (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2020)
Rāmānuja is one of the great exponents of the bhakti-Vedānta Philosophy, which known as Vaiṣṇava. He advocates the doctrine of Viśistādvaita or monism, which possess traits. Two of his most influential works, Vedārtha-Saṃgraha and Śrī-Bhāṣya, are detailed commentaries on Vedanta Sutra. From these two great works, thoughts about the divine philosophy of Śrī Rāmānuja can be interpreted and patterned. Refuting other theistic systems, Rāmānuja reconciles the concepts of Nirguna Brahman and Saguna Brahman by asserting that Brahman as Narayana is an ocean of auspicious attributes even though his exact form is pure and blissful knowledge.